El juego y su relación con el desarrollo psicomotriz de los niños y niñas de educación inicial 2 de la escuela Febres Cordero y centro infantil Caritas Alegres del cantón Marcabelí, provincia de El Oro, período lectivo 2013-2014. Lineamientos alternativos - Jimbo Orozco, Rocío Elizabeth (2014)
This thesis refers to "THE GAME AND ITS RELATION TO THE CHILDREN PSYCHOMOTOR DEVELOPMENT OF TWO EARLY CHILDHOOD EDUCATION “FEBRES LAMB” SCHOOL "CARITAS ALEGRES” CHILD CENTER, MARCABELÍ CANTON, EL ORO PROVINCE, PERIOD 2013 - 2014." ALTERNATIVE GUIDELINES, made according to the provisions of Academic Rules System, National University of Loja. The General Objective was Determine the Game impact on the Psychomotor Development of Children 2 in Early Childhood Education, “Febres Cordero School" and " Caritas Alegres Center” Marcabelí Canton, El Oro Province 2013-2014 period . The methods used for the preparation of this research work were: scientific, inductive, deductive, analytical, Synthetic, Descriptive, and Statistical Model, which served them to help efficiently achieve the goal. The techniques and instruments used were an elaborate survey and applied to teachers of children Early Childhood Education 2 " Febres Cordero School," and " Caritas Alegres Center” Marcabelí Canton, El Oro Province ; to identify the types of playing and strategies Ability Test lúdicas.y Powertrain Ozeretsky applied to children early education 2 " Febres Cordero School," and " Caritas Alegres Center” Marcabelí Canton, El Oro Province , period school 2013 - 2014 ; to evaluate the Psychomotor Development . According to the survey results the teachers concluded that: the 100% of teachers surveyed report that the game types that are most often done engines and social interaction Games, symbolic Games, rules, and Games construction; and 50% fiction or fantasy games The game has deep relationship not only with the development of skills and intellectual abilities but also with the development of, free and happy emotional states. Analyzed the results of the Test of Motor Proficiency Oseretzky concluded that: the 81% of children in, have a Development psychomotor and the 19% Satisfactory Unsatisfactory. The Psychomotor Development is the psychological and muscle maturity that a person, in this case a child. Psychological aspects and muscle are the variables that constitute the behavior or attitude.